Partycypacja społeczna młodzieży i jej wartościowanie. Analiza socjologiczna - Szymczak, Wioletta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The aim of this article is firstly to analyse the levels of young people’s social participation, along with its selected determinants. Secondly, the aim is to answer the question: how do the research participants value voluntary initiatives and actions proposed at school? Research findings by representatives of social sciences concerning the situation of modern-day young people, their social participation, passive attitudes and on the issue of civic education constitute a reference point for the discussion. Subject to analysis are outcomes of representative sociological research conducted among adult young people attending secondary schools in the Archdiocese of Lublin in 2020 and 2021. The paper discusses the declared statements of the respondents on their participation in non-compulsory groups and initiatives organized at school, as well as in extra-curricular, pro-social organizations and actions. The statistical analyses included the following independent variables: sex, place of residence and religiosity measured by attitude towards faith, chi-square and Cramer’s V tests. The conclusions show among others that the respondents exhibit a low level of social participation. They highlight the potential to be found in their positive valuation of various forms of engagement as well as their willingness to take part in actions that aim at helping others in the future.